“El aprendizaje basado en problemas y su relación con la enseñanza de la cinemática con los estudiantes de primer año de bachillerato paralelo “a”, de la unidad educativa “Amelia Gallegos Díaz”, durante el año lectivo Septiembre 2015-Enero 2016”. - Yuquilema Saez, Norma Fabiola (2016)
Education is an essential part of every individual and henc of a society which seeks to achieve its development to be competitive, this requires a full education and quality. The present investigation whose theme is: THE PROBLEM BASED LEARNING AND ITS RELATIONSHIP WITH THE TEACHING OF THE KINEMATICS WITH THE STUDENTS FROM THE FIRST YEARS OF AMELIA GALLEGOS HIGH SCHOOL, DURING THE SCHOOL YEAR SEPTEMBER 2015-JANUARY 2016. Seeks to improve the learning difficulties through team work, on the basis of the phenomena that happen in our daily living and theories already laid down by the great masters of physics and pedagogy, to achieve a significant learning of Ausubel, for based on the degree of knowledge that the student has and the theory of Barrows which the work in groups and applying more problems to help the students better develops its capacity of reasoning. About the population worked are 150 students, distributed in five parallels. By using the sample of 33 students a methods of work for this research was developed as a correlational design. The techniques used for data collection were the survey and observation as a tool we use the questionnaire and the checklist the result after applying the (ABP) was satisfactory in relation to the traditional approach because the students aroused the curiosity to learn to improve their knowledge allowing comply with the objectives set at the beginning of the investigative process, in this way was able to verify the hypothesis, coming to the conclusion that the problem-based learning influences satisfactorily in the learning of kinematics.